Psycholinguistic Examination of Language Ethics in Everyday Communication: Insights from Five-Year-Olds - Ulin Nafiah; Hanna Hanna; La Ino (Halu Oleo University, 2023)
This qualitative study delves into the intricacies of language ethics exhibited by a five-year-old child named Dzakwan, drawing upon transcribed audio recordings spanning March to May 2020. Situated within the multifaceted framework of human development encompassing biological, cognitive, and socio-emotional processes, the research seeks to elucidate the factors shaping language ethics acquisition in early childhood. Through descriptive analysis, the study unveils Dzakwan's adeptness in adhering to linguistic norms, attributable to a confluence of influences including health, cognitive prowess, learning experiences, and environmental stimuli. These findings underscore the nuanced interplay between individual characteristics and external factors in the cultivation of language ethics. Furthermore, practical implications emerge, suggesting strategies to nurture language proficiency and ethical communication in young children, such as fostering meaningful dialogue and cultivating responsive interactions within their social milieu. By shedding light on the developmental trajectory of language ethics, this research contributes to a deeper understanding of language acquisition processes and offers actionable insights for promoting linguistic competence in early childhood education and parental guidance.